2021
DOI: 10.1177/1750458920982168
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pathway signage for operating theatres

Abstract: On 20 August 2020, Public Health England released a new version of the ‘COVID-19: Guidance for the remobilisation of services within health and care settings: infection prevention and control recommendations’, superseding that of 18 June 2020. In this document, the infection prevention and control principles determine that the treatment, care and support of patients are to be managed in three COVID-19 pathways. These are: ‘high risk’, ‘medium risk’ and ‘low risk’. In the operating theatre, where procedures may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Research has shown that a high level of visibility enhances staff awareness and team communication [ 25 ]. During the pandemic, hospitals put up signage, called the ‘COVID-19 flag’, which provided a quick visual guide [ 26 ]. Even though many studies have reported the benefits of good wayfinding signs in hospitals [ 27 ], more studies are needed to establish the scientifically validated benefit of an intuitive signage for caution.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that a high level of visibility enhances staff awareness and team communication [ 25 ]. During the pandemic, hospitals put up signage, called the ‘COVID-19 flag’, which provided a quick visual guide [ 26 ]. Even though many studies have reported the benefits of good wayfinding signs in hospitals [ 27 ], more studies are needed to establish the scientifically validated benefit of an intuitive signage for caution.…”
Section: Resultsmentioning
confidence: 99%